Bottom ash effect in portland cement composite performance - Ng, Hooi Jun (School of Materials Engineering, 2018)
Scope of this research is to centralize on the investigation of the effect, mechanical behaviour, and performance of bottom ash in Portland cement determine through the density, compressive strength test, pozzolanic activity index, acid resistance, fire resistance, durability. Besides that, materials characteristics also will be evaluated according to the various percentage of bottom ash in Portland cement by morphology, mineralogical, and ternary phase analysis at UniMAP laboratory. For each topic, a literature survey was performed to identify the characteristic of Portland cement and bottom ash cement composite.